Cubic-quartic embedded solitons with χ(2) and χ(3) nonlinear susceptibilities having multiplicative white noise via Itô calculus. (March 2023) - Zayed, Elsayed M.E.; Alngar, Mohamed E.M.; Shohib, Reham M.A.
Abstract: The objective of this paper is to study the cubic-quartic embedded solitons with χ ( 2 ) and χ ( 3 ) nonlinear susceptibilities having multiplicative white noise in the Itô sense. The unified Riccati equation expansion method and the addendum Kudryashov's method are employed to accomplish this task. The straddled soliton, the combo bright-singular soliton, the bright soliton, the singular soliton solutions as long as periodic and rational solutions are obtained. The numerical schemes give a visual perspective to the solutions derived analytically. Highlights: The objective of this paper is to study the cubic-quartic embedded solitons with χ ( 2 ) and χ ( 3 ) nonlinear susceptibilities having multiplicative white noise via Itô calculus. The unified Riccati equation expansion method and the addendum Kudryashov's method are employed to accomplish this task. The straddled soliton, the combo bright-singular soliton, the bright soliton, the singular soliton solutions as long as periodic and rational solutions.